Impact of Edible Insect Polysaccharides on Mouse Gut Microbiota: A Study on White-Spotted Flower Chafer Larva (Protaetia brevitarsis seulensis) and Silkworm Pupa (Bombyx mori) - Joon-Ha Lee; Hyojung Son; Sathiyamoorthy Subramaniyam; Hyun-Jung Lim; Sohyun Park; Ra-Yeong Choi; In-Woo Kim; Minchul Seo; Hae-Yong Kweon; Yongsoon Kim; Seong-Wan Kim; Jong-Soon Choi; et al. (Foods)
The increasing global population and the environmental consequences of meat consumption have led to the exploration of alternative sources of protein. Edible insects have gained attention as a sustainable and nutritionally rich meat alternative. We investigated the effects of two commonly consumed insects, Protaetia brevitarsis seulensis larva and Bombyx mori pupa, on beneficial gut microbiota growth, using whole 16s metagenome sequencing to assess diet-associated changes. Seven-week-old female C57BL/6J mice were administered the edible insects, along with fracto-oligosaccharide (FOS) as a positive control and sham (phosphate buffer saline (PBS)) as a negative control, to assess the relative abundance of insect-diet-associated gut microbes. In total, 567 genera and 470 species were observed, and among these, 15 bacterial genera were differentially abundant in all three groups. These results show that among the two insects, Bombyx mori pupa polysaccharides have a greater ability to regulate beneficial probiotics and next-generation probiotics. In particular, Lactococcus garvieae, which has promising effects on the gastrointestinal tracts of humans and animals, was significantly enriched in both Protaetia brevitarsis seulensis larva and Bombyx mori pupa polysaccharides, similar to fracto-oligosaccharide. The results suggest that the consumption of these insects, particularly polysaccharides, can enhance the growth of beneficial gut microbes, potentially leading to improved overall health in healthy populations.